Integrating the Islamic Worldview into the Planning of Neighbourhoods - Omer, Spahic (Penerbit Universiti Sains Malaysia, 2007)
This paper aims to highlight the importance of integrating the Islamic worldview into the aspects of planning, in general, and into the planning of neighbourhoods, in particular. In this paper I shall examine, firstly, the pertinence of the Islamic worldview to the notion of planning neighbourhoods. There we will see that such an enterprise was an integral part of Islamic urbanism from the era of the Prophet Muhammad (pbuh) till the waning of Islamic civilization. As such, no successful establishment of contemporary Islamic urbanism without integrating the same with the Islamic worldview can ever be possible. Next, the following principles will be discussed: (i) the Islamic idea of the settlement, (ii) Islam on creating buildings, (iii) peaceful co-existence with the environment, and (iv) Islam on human dignity and fraternity among its members. Discussion on each of the mentioned principles will be followed by briefly analyzing their implications for the planning of neighbourhoods. Some suggestions as to how to make the notion of integrating the Islamic worldview into the idea of planning appear relevant and appealing to the Muslims of today will also be presented. While writing the paper, I have tried as much as possible to draw on the most relevant sources that deal with the theme at hand, the most important of which, certainly, are the Holy Qur'an and the authentic compilations of the Prophet Muhammad's words and actions